Improving clinical outcomes in treating heroin dependence: randomized, controlled trial of oral or implant naltrexone - Hulse, G.; Morris, N.; Arnold-Reed, D.; Tait, Robert (American Medical Association, 2009)
CONTEXT: Oral naltrexone hydrochloride effectively antagonizes heroin, but its utility is limited by patient noncompliance. Sustained-release preparations may overcome this limitation.OBJECTIVE: To compare the safety and efficacy of a single-treatment sustained-release naltrexone implant with daily oral naltrexone treatment.DESIGN: Seventy heroin-dependent volunteers entered a randomized, double-blind, double-placebo controlled trial with a 6-month follow-up period.PATIENTS: Eligibility criteria were DSM-IV opioid (heroin) dependence; age 18 years or older; willingness to be randomized; residing in the Perth, Western Australia, metropolitan area; and completion of preclinical screening and written consent. A total of 129 eligible participants were identified, and 70 (54%) provided informed consent and were randomized as per the study design.INTERVENTION: Participants received oral naltrexone, 50 mg/d, for 6 months (plus placebo implants) or a single dose of 2.3 g of naltrexone implant (plus placebo tablets).MAIN OUTCOME MEASURES: (1) Maintaining therapeutic naltrexone levels above 2 ng/mL; (2) return to regular heroin use (>or=4 d/wk); (3) other heroin use and abstinence; (4) use of illicit nonopioid drugs; (5) number of opiate overdoses requiring hospitalization; (6) treatment-related unexpected and expected adverse events; and (7) blood naltrexone levels (ie, pharmacokinetic profile) for recipients of active naltrexone implants.RESULTS: More participants in the oral vs the implant group had blood naltrexone levels below 2 ng/mL in months 1 (P < .001) and 2 (P = .01); in addition, more oral group participants had returned to regular heroin use by 6 months (P = .003) and at an earlier stage (median [SE], 115 [12.0] days vs 158 [9.4] days). There were 10 trial-related, unexpected adverse events. One serious adverse event, a wound hematoma, was associated with surgical implantation. Naltrexone blood levels in implant recipients were maintained above 1 and 2 ng/mL for 101 (95% confidence interval, 83-119) and 56 (39-73) days, respectively, among men and 124 (88-175) and 43 (16-79) days among women.CONCLUSIONS: The naltrexone implant effectively reduced relapse to regular heroin use compared with oral naltrexone and was not associated with major adverse events. Clinical Trial Registration anzctr.org.au Identifier: ACTRN12606000308594